Trends of maternal mortality at a tertiary health care centre in India - Kapote, Deepali S.; Syed, Anam B.; Gawai, Swati C.; Desai, Ashwini S.; Mohite, Apeksha M. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: Maternal mortality is the death of a woman while pregnant or within 42 days of termination of pregnancy, irrespective of duration and site of pregnancy from any cause, related to or aggravated by the pregnancy or its management but not from accidental or incidental causes. Methods: A retrospective study was conducted by reviewing the hospital records to study the maternal deaths and complication leading to maternal death over the period of one year from January 2019 to December 2019 in the department of obstetrics and gynecology, LTMMC and Sion Hospital. Results: The maternal mortality ratio in the present study 548/100000 live births and corrected MMR’s 190/live births. There were 49 deaths of 8093 live birth during the study period. The majority of deaths occurred in the 20-30 age group. Hemorrhage (22.4%) and hypertensive disorder (14.2%) are two most common direct cause of maternal deaths. 46.9% of maternal deaths occurred after 72 hours of death. Indirect cause accounts for 73.5%. Of these deaths and DIC with sepsis was the leading indirect cause of maternal deaths. Conclusions: Hemorrhage, hypertensive disorder, anemia and DIC with sepsis remain major cause of maternal deaths. Delay at primary level, by the patient and family contributed to higher maternal mortality. This requires more effort to educate, impart knowledge to recognize danger signs and seek urgent medical help and create awareness about the easy accessibility and availability of nearby health care facilities amongst the society.